A Study to Assess Knowledge Regarding Preparation and Use of Audio-Visual Aids among Nursing Students of Selected Nursing College - P. Joseph, Rajesh; E.V. , Nirmal Raj; Belagavi, Dayanand; Shital, Damor; Yagnika, Damor; Vanshika, Darji; Pranav, Devani (International Journal of Psychosocial Rehabilitation, 2020)
Background: Audiovisual aids are a helpful supplement to the nursing curriculum. They are the rich resources for nurse educators and nursing students in the field of health care. The mode in which a subject matter is taught will influence the knowledge and interest of the students. Incorporating audiovisual aids in the nursing curriculum will keep the students’ concentration high. Aim: Prearranged educational materials induce the learners to learn concretely. In that respect, the investigator aimed to assess the knowledge regarding the preparation and use of audio-visual aids among undergraduate nursing students. Material and Methods: A descriptive, exploratory study was conducted among 182 undergraduate nursing students of selected nursing colleges in Vadodara. The samples were recruited by purposive sampling technique. Priorly the investigators explained the purpose of the study to the participants and obtained written consent. The data was obtained by a structured knowledge questionnaire consisting of 40 questions through the interview method. Based on the scoring interpretation, the respondent’s level of knowledge was categorized into adequate knowledge, moderately adequate knowledge, and inadequate knowledge. The investigator carried out descriptive and inferential statistics to analyze the data. Results: The results exposed that there is no significant association between existing knowledge and selected socio-demographic variables of the respondents. Assessment of knowledge revealed that only 1.09% (2) of the respondents had adequate knowledge, 70.32% (128) of the respondents expressed moderately adequate knowledge, and 28.57% (52) of the samples exhibited inadequate knowledge. Conclusion: An audiovisual aid occupies a crucial role in the nursing curriculum, which enhances the nursing student’s knowledge and skills. It was understood from the present study that a knowledge gap exists in the preparation and use of audio-visual aids among undergraduate nursing students. Hence, we recommend that interventional studies be conducted extensively in order to enhance the knowledge of the students.